Evaluating the Effect of Resin-Reinforced Fiber Splint Application on the Stabilization of Mandibular Corpus Fractures: An in Vitro Study - Ertan Yalçin; Mehmet Zahit Baş (Atatürk University, 2024)
Objective: This study aimed to evaluate the efficiency of a resin-supported fiber splint in the dental area as a fixation method in order to avoid the disadvantages of using a second plate in mandible corpus fractures Methods: 24 cadaveric sheep hemimandibulae were randomly divided into four groups. The biomechanical stability of four different groups in which four different fixation methods were applied was evaluated. A single miniplate was used in Group A, and a double miniplate was used in Group B. In Group C, an arch bar was applied along the dental arch with a single mini-plate. In Group D, a single mini-plate was supported by fiber splinting along the dental arch. Results: The average force values were found at the highest level in the single-plate arch bar group and the lowest in the single-plate group. Looking at the data shown, the single plate arch bar group showed the highest stability, and the single- plate group showed the lowest stability. The mean displacement values were highest in the single-plate arch bar group and lowest in the single-plate group. The aforementioned data coincides with the maximum force values. Conclusion: It has been noted that the fiber splint application, which was used to avoid the disadvantages of the arch bar application, contributed positively to the stability of fracture fixation. Keywords: Fracture, Mandible, Fiber Splint Mandibular Korpus Kırıklarında Rezinle Güçlendirilmiş Fiber Splint Uygulamasının Stabilizasyon Üzerine Etkisinin Araştırılması: İn Vitro Çalışma ÖZ Amaç: Bu çalışmanın amacı, mandibula korpus kırıklarında ikinci bir plak kullanımının dezavantajlarından kaçınmak için, bir fiksasyon yöntemi olarak dental bölgede uygulanan rezin destekli fiber splintin etkinliğini değerlendirmektir. Yöntemler: 24 kadavra koyun hemimandibulası rastgele 4 gruba ayrıldı. 4 farklı fiksasyon yönteminin uygulandığı 4 farklı grubun biyomekanik stabiliteleri değerlendirildi. Grup A'da tek miniplak, Grup B'de çift mini-plak kullanıldı. Grup C'de tek mini-plak ile dental ark boyunca ark bar uygulanmıştır. D grubunda ise tek bir mini-plak dental ark boyunca fiber splint uygulaması ile desteklenmiştir. Bulgular: Ortalama kuvvet değerleri tek plakalı arch bar grubunda en yüksek, tek plak grupta ise en düşük seviyede bulunmuştur. Gösterilen verilere bakıldığında, tek plakalı arch bar grubu en yüksek stabiliteyi, tek plaklı grup ise en düşük stabiliteyi göstermiştir. Ortalama yer değiştirme değerleri tek plak arch bar grubunda en yüksek, tek plak grupta ise en düşüktür. Söz konusu veriler maksimum kuvvet değerleri ile örtüşmektedir. Sonuç: Ark bar uygulamasının dezavantajlarından kaçınmak için kullanılan fiber splint uygulamasının kırık fiksasyonunun stabilitesine olumlu katkı sağladığı kaydedilmiştir.. Anahtar Kelimeler : Fraktür, Mandibula, Fiber Splint